(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Bridge collapses are catastrophic infrastructure failures, leading to loss of life, disruption of mobility, and erosion of public trust. This paper analyses four major Indian bridge collapses (2013–2025) — Ultadanga, Talkies, Taratala (Majerhat), and Gambhira — using a Case–Cause–Lesson framework. A comparative study of Majerhat (2018) and Gambhira (2025) is presented to highlight recurring weaknesses in design, construction, maintenance, governance and have revealed severe deficiencies in structural health monitoring, inspection protocols, and disaster preparedness. This paper integrates case-based forensic analysis with international benchmarking to identify systemic gaps in bridge safety management. Using a mixed qualitative–quantitative framework, the study examines causes, consequences, and institutional responses to recent bridge failures. A comparative overview of international best practices (Japan, UK, USA) informs a roadmap for implementing IoT-based Bridge Health Monitoring (BHM) and Digital Twin frameworks in Indian conditions. Results highlight the urgent need for integrated governance, transparent maintenance systems, and community-focused disaster management protocols.